Rhizolutin directly dissociates Aβ and tau aggregates and reduces apoptosis/inflammation related to Alzheimer's disease. (31st December 2021) - Shin, Jisu; Kwon, Yun; Nam, Kwangho; An, Joon Soo; Yang, Seung‐Hoon; Hong, Seong‐Heon; Bae, Munhyung; Moon, Kyuho; Cho, Yakdol; Woo, Jiwan; Park, Keunwan; Kim, Kyeonghwan; et al.
Abstract: Background: Alzheimer's disease (AD) is characterized by the aggregation of amyloid‐β (Aβ) and tau, leading to neuronal cell death, neuroinflammation, and brain atrophy. As Aβ and tau aggregates are observed in the brain decades before the onset of cognitive symptoms, clearance of these aggregates has been widely accepted for AD treatments. Method: Through the unbiased screening against the natural product libraries, rhizolutin was selected and its regulatory effects on Aβ and tau aggregation were validated by thioflavin T assays. Clearance of Aβ plaques was observed in APP/PS1 double transgenic AD model mice and subsequent analyses regarding apoptosis and inflammation were conducted using neuronal and glial cell lines. Result: Rhizolutin‐treated AD model mice significantly decreased hippocampal Aβ plaques. Additionally, rhizolutin effectively inhibited the aggregation of Aβ and tau in vitro, more importantly, dissociated both aggregates, thereby reducing Aβ‐induced apoptosis and inflammation in neuronal and glial cells. Conclusion: Our findings reveal that a unique chemical rhizolutin regulates both Aβ and tau at the same time by therapeutic and preventive approaches, representing its novel structure is attractive for AD drug discovery.